Dicyclohexanyl Orizane Constituent from the Hulls of Oryza sativa and its Inhibitory Activity - Chung, Ill-Min; Ali, Mohd; Ahmad, Ateeque (Asian Journal of Chemistry, 2016)
From the hulls of Oryza sativa was isolated one new compound dicyclohexanyl orizane (1) along with several known compounds hentriacontane, 1-tetratriacontanol, b-sitosterol, momilactones A, B, tricin, b-sitosterol-3-O-b-D-glucuronoside, 3,7-dimethyl-n-octan-1-yl benzoate and b-sitosterol-3-O-b-D-glucoside. The structure of the new compound was elucidated by 500 MHz NMR using 1D and 2D spectral methods, viz., 1H, 13C, 1H-1H COSY and HETCOR aided by EIMS, FABMS and IR. The compound 1 was found to have no inhibitory effects against duckweed Lemma paucicostata Hegelm 381).